Procedure in Civil Proceedings - Татулич, Ірина Юріївна (European Reforms Bulletin: scientific peer-reviewed journal, 2015)
the article reveals the essence, meaning and notion of procedure in civil proceedings. The author of the article has carried out the comparative characteristics of the procedure with other legal categories. Procedure in civil proceedings are also defined and generalized. On the basis of all the investigations the author definition of the notion “procedure” is formed.
Keywords: procedure; process; civil proceedings; procedural order; civil procedural form; writ proceedings; writ.